Effects of a participatory work stress prevention approach for employees in primary education: results of a quasi-experimental study - Maartje C Bakhuys Roozeboom; Noortje M Wiezer; Roosmarijn MC Schelvis; Irene MW Niks; Cécile RL Boot (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: Work stress is a serious problem for employees in primary education. This study evaluates the effects of a work stress prevention approach on emotional exhaustion and work stress determinants (job crafting behavior, quantitative and emotional demands, leadership, support, autonomy, team culture and feelings of competence), and the impact of implementation success (management commitment, employee involvement, communication during implementation) on these outcomes. METHODS: A quasi-experimental study was conducted with an intervention group (4 schools, N=102 employees) and a control group (26 schools, N=656 employees) using questionnaires at baseline (T0), one-year (T1) and two-year (T2) follow-up. Multilevel mixed model analyses were performed to test effects of condition and implementation success on changes in emotional exhaustion and work stress determinants between T0 and T2 in the intervention and control group. RESULTS: No effect were found for emotional exhaustion. Improvement of quality of leadership between T0 and T2 was significantly larger in the intervention compared to the control group. Additionally, implementation success was associated with a decrease in unnecessary demands and an increase in quality of leadership, team culture and job crafting behavior. CONCLUSIONS: This study shows no direct effect of the approach on emotional exhaustion, but it does show beneficial effects on quality of leadership. Additionally, results suggest that, when successfully implemented, the approach also has beneficial effects on other work stress determinants (ie, job crafting behavior, unnecessary demands and team culture). Results indicate that - if implemented successfully - the organizational-level intervention has the potential to improve the psychosocial work context.